Reevaluating the Formal Requirements of Wills: Advocating for the Integration of Electronic Wills - Lilian Ifeoma Nwabueze; Peter Ikechukwu Gasiokwu (Khazanah Hukum, 2024)
This paper aims to examine the nature and purpose of the formal requirements of Wills, highlighting their limitations and the need for adaptation in the context of modern electronic communication. The doctrinal research method was employed to evaluate legal problems and analyse the current statutory framework governing Wills. The study found that the traditional formal requirements for Wills, intended to provide testamentary protection and serve as legal proof of execution, often fail to meet their purpose effectively. Judicial and judicious applications of these rules have revealed significant limitations. There is an urgent need for the law to adapt to technological advancements by incorporating electronic Wills. This adaptation would address the inadequacies of current formal requirements and ensure the effectiveness of testamentary dispositions as evidenced in its use in South Africa by all categories of persons- with or without legal knowledge; in the United States of America for exigencies and in Australia to ensure high level of confidentiality and secrecy. The paper recommends articulated formalities supported by electronic communication to achieve testamentary goals. It suggests amendments to the extant laws on Wills in jurisdictions where provisions for dispensing powers are missing while detailed and applicable electronic Will legislation is recommended for jurisdictions that have long recognized the need for testamentary disposition to join the global advancement in technology.